Perceived social support, loneliness and anxiety among Malaysian undergraduate students during the covid-19 - Tan, Lei Gee (2022)
In recent years, the Coronavirus disease (COVID-19) has caused significant anxiety globally. This research aims to examine the relationships between anxiety, loneliness, and perceived social support in three dimensions, which are family support, friends’ support, and significant others’ support among undergraduate students in Malaysia. A cross-sectional study with 111 undergraduate students was conducted using the purposive sampling approach. The online survey was used to collect a large number of data. There are more female respondents (n = 65, 58.56%) than male respondents (n = 46, 41.44%) in this study who were between the age of 18 to 25 (M = 22.18, SD = 1.78). The instruments applied in this study are the Generalized Anxiety Disorder-7 Scale (GAD-7), Multidimensional Scale of Perceived Social Support (MSPSS), and UCLA-3 Loneliness Scale. The result showed that anxiety was significantly negatively correlated with perceived social support. The same findings also showed that anxiety which was having a significant negative relationship with perceived family support, friends’ support, and significant others’ support. On the other hand, loneliness showed a positive correlation with anxiety levels. Additionally, no gender difference was found in the present research. This study offers a constructive framework to mental health professionals and counsellors on how social supports influence individual mental health, so they can provide a suitable intervention for undergraduate students in dealing with anxiety and loneliness.